PENYULUHAN HUKUM TENTANG PERLINDUNGAN HUKUM DALAM SENGKETA PERDATA DI MASYARAKAT - Gunawan Widjaja (Lafadz Jaya Publisher, 2026)
This article discusses legal education on legal protection in civil disputes within the community. The main issue raised is the public’s limited understanding of their legal rights and obligations, which often leads to civil disputes arising from breach of contract, unclear agreements, or a lack of knowledge regarding dispute resolution mechanisms. This study employs a literature review method, examining various legal sources, books, journals and relevant regulations to understand the concept of legal protection and the mechanisms for resolving civil disputes. The findings indicate that legal protection in civil disputes encompasses two main forms: preventive and repressive protection. Preventive protection serves to prevent disputes from arising through legal education and advice, whilst repressive protection provides avenues for resolution through litigation or non-litigation means such as mediation and negotiation. Consequently, legal advice serves as a vital means of raising public legal awareness, enabling citizens to protect their rights more effectively.